Wild learning : practical ideas to bring teaching outdoors - Tidd, Rachel (John Wiley & Sons, Inc., 2023)
"Outdoor learning has been rising in popularity in the U.S. during the last decade, particularly at the early childhood level. This growing interest has spread to the elementary level, with families demanding more time learning and playing outdoors for children during the school day. Being outside is healthier, helps children form a strong connection with the natural world, supports a variety of learning styles, increases engagement and student motivation to learn all by simply moving instruction outdoors! In addition, the mental health benefits of outdoor learning have been well documented. Schools continue to struggle to meet learning and mental health needs of their students. Incorporating more outdoor learning in schools is a simple and cost-effective way to provide support to students"--